2020
DOI: 10.1097/pcc.0000000000002276
|View full text |Cite
|
Sign up to set email alerts
|

Readiness for Hospital Discharge, Stress, and Coping in Mothers of Children Undergoing Cardiac Surgeries: A Single-Center Prospective Study

Abstract: Objectives: To examine the relationship between stress, coping, and discharge readiness in mothers of children undergoing congenital heart surgeries. Design: Quantitative descriptive study at three time points: pre surgery (time point I), day of hospital discharge (time point II) and 2 weeks following discharge (time point III). Setting: Tertiary care pediatric hospital in Singapore. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 33 publications
0
6
0
Order By: Relevance
“…Ten instruments used to evaluate stress and strain experienced in the parenting role, including in the context of illness were identified across 30 (28%) distinct samples. Seven instruments of parenting stress ( Abidin, 2012 ; Barsella et al, 2021 ; Haverman et al, 2013 ; Östberg et al, 1997 ; Streisand et al, 2001 ; Jantien Vrijmoet-Wiersma et al, 2010 ) were identified across 27 distinct samples ( Barsella et al, 2021 ; Bishop et al, 2019 ; Brosig et al, 2007a ; Carey et al, 2002 ; Caris et al, 2016 ; Chaisom et al, 2010 ; Chang et al, 2020 ; Choi & Lee, 2021 ; De Stasio et al, 2019 ; Ezzat et al, 2016 ; Goldberg et al, 1991 ; Golfenshtein et al, 2017 ; Jackson et al 2020 ; Kaugars et al, 2018 ; Lee et al, 2007 ; Majnemer et al, 2006 ; Medoff-Cooper et al, 2020 ; Mörelius et al, 2002 ; Poh et al, 2020 ; Mussatto et al, 2021 ; Re et al, 2018 ; Sarajuuri et al, 2012 ; Torowicz et al, 2010 ; Uzark & Jones, 2003 ; van der Mheen et al, 2019 ; Visconti et al, 2002 ; Jantien Vrijmoet -Wiersma et al, 2009 ). Most frequently used were the Parenting Stress Index ( Abidin, 2012 ) and the Parenting Stress-Short Form ( Abidin, 2012 ) across 8 and 12 studies, respectively, including Dutch, Korean, Arabic, Chinese, and Thai translations of the Parenting Stress Index-Short Form.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Ten instruments used to evaluate stress and strain experienced in the parenting role, including in the context of illness were identified across 30 (28%) distinct samples. Seven instruments of parenting stress ( Abidin, 2012 ; Barsella et al, 2021 ; Haverman et al, 2013 ; Östberg et al, 1997 ; Streisand et al, 2001 ; Jantien Vrijmoet-Wiersma et al, 2010 ) were identified across 27 distinct samples ( Barsella et al, 2021 ; Bishop et al, 2019 ; Brosig et al, 2007a ; Carey et al, 2002 ; Caris et al, 2016 ; Chaisom et al, 2010 ; Chang et al, 2020 ; Choi & Lee, 2021 ; De Stasio et al, 2019 ; Ezzat et al, 2016 ; Goldberg et al, 1991 ; Golfenshtein et al, 2017 ; Jackson et al 2020 ; Kaugars et al, 2018 ; Lee et al, 2007 ; Majnemer et al, 2006 ; Medoff-Cooper et al, 2020 ; Mörelius et al, 2002 ; Poh et al, 2020 ; Mussatto et al, 2021 ; Re et al, 2018 ; Sarajuuri et al, 2012 ; Torowicz et al, 2010 ; Uzark & Jones, 2003 ; van der Mheen et al, 2019 ; Visconti et al, 2002 ; Jantien Vrijmoet -Wiersma et al, 2009 ). Most frequently used were the Parenting Stress Index ( Abidin, 2012 ) and the Parenting Stress-Short Form ( Abidin, 2012 ) across 8 and 12 studies, respectively, including Dutch, Korean, Arabic, Chinese, and Thai translations of the Parenting Stress Index-Short Form.…”
Section: Resultsmentioning
confidence: 99%
“…Instruments explicitly identifying assessment of coping, including coping self-efficacy and coping appraisal, were categorized in this section. The full, modified version, and subscale-only usage of 12 instruments of coping ( Carver, 1997 ; Carver et al, 1989 ; Chesney et al, 2003 ; Endler & Parker, 1994 ; Folkman & Lazarus, 1985 ; Frydenberg & Lewis, 2014 ; Jackson et al, 2017 ; McCubbin et al, 1981 ; Murphy et al, 2017 ; Schreurs, 1993 ; Sira et al, 2014 ) were identified across 19 (17%) studies and 18 samples ( Ahn et al, 2014 ; Berant et al, 2001 , 2003 ; Choi & Lee, 2021 ; Davis 1998 ; Diffin et al, 2016 ; Doherty et al, 2009 ; Hancock et al, 2018 ; Jackson et al, 2020 ; Miller et al, 2021 ; McCusker et al, 2010 ; Mussatto et al, 2021 ; Poh et al 2020 ; Roberts et al, 2021 ; Rychik et al, 2013 ; Sira et al, 2014 ; Spijkerboer et al 2007 ; Svavarsdottir & McCubbin, 1996 ; Utens et al, 2000 ). The most frequently used instrument was the Coping Health Inventory for Parents ( McCubbin et al, 1981 ) in five studies across the USA and Singapore, with two studies ( Jackson et al, 2020 ; Sira et al, 2014 ) using multiple coping instruments.…”
Section: Resultsmentioning
confidence: 99%
“…The hospital environment serves as an important stressor for children when seeking a doctor, and the medical and nursing procedures can easily have a negative impact on the experience for children ( 1 ). Even minor surgeries or routine treatments can cause pain and anxiety in children.…”
Section: Introductionmentioning
confidence: 99%
“…This result has led to a shift in focus from survival to long‐term care issues, such as follow‐up practices and psychosocial consequences. Caring for a child with CHD is stressful, and patients may require multiple interventional therapies, surgical procedures, life‐long medication and nursing interventions (Poh et al., 2020; van der Linde et al., 2011), representing substantial economic and mental pressures on the family (Faraoni et al., 2016; McClung et al., 2018).…”
Section: Introductionmentioning
confidence: 99%